Analisis Risiko Ergonomi Postur Kerja Dokter Gigi Menggunakan Rapid Upper Limb Assessment (RULA) dan Nordic Body Map (NBM) - Andhini Kumala; Roberta Zulfhi Surya; Wahmin Rais (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Dentists are at high risk of developing musculoskeletal disorders (MSDs) due to prolonged static working postures, repetitive movements, and continuous use of dental instruments. This study aimed to analyze the relationship between ergonomic risk based on working posture using the Rapid Upper Limb Assessment (RULA) method and musculoskeletal complaints identified using the Nordic Body Map (NBM) among dentists in Padang City. This research employed a cross-sectional study design involving 35 dentists selected through purposive sampling. The relationship between RULA and NBM scores was analyzed using Spearman’s rank correlation test. The results showed a strong and statistically significant positive correlation between RULA and NBM scores (r = 0.959; p = 0.000). The majority of respondents were classified as having a high ergonomic risk level (62.9%) and a high level of musculoskeletal complaints (62.9%). The highest prevalence of complaints was found in the upper neck (85.7%), lower back (82.9%), and lower neck (80.0%). These findings indicate the need for ergonomic interventions to reduce the risk of musculoskeletal disorders among dentists.